Parity nonconservation effect in the resonance elastic electron scattering on heavy He-like ions - Zaytsev, Vladimir; Tashenov, Stanislav; Maiorova, A. V.; Shabaev, V. M.; Stöhlker, Th (Journal of physics. B, Atomic, molecular and optical physics, 2015)
We investigate the parity nonconservation effect in the elastic scattering of polarized electrons on heavy He-like ions, being initially in the ground state. The enhancement of the parity violation is achieved by tuning the energy of the incident electron in resonance with quasidegenerate doubly-excited states of the corresponding Li-like ion. We consider two possible scenarios. In the first one we assume that the polarization of the scattered electron is measured, while in the second one it is not detected. For the second scenario we propose a scheme of a modified electron beam ion source (EBIS) experiment where the detection of a parity violation in the electron scattering seems possible.